P750 Biosimilar Infliximab Switching is Not Associated with Adverse Outcomes: A Real-World Effectiveness Analyses in a National U.S. Cohort of U.S. Military Veterans with Inflammatory Bowel Disease. (30th January 2023) - Hou, J K; Pham, C; Sansgiry, S; Modi, V; Waljee, A K
Abstract: Background: Infliximab (IFX) biosimilars are widely available for Crohn's disease (CD) and ulcerative colitis (UC). However, implementation of biosimilar switching has been highly variable in the U.S. Barriers to switching include patient and provider concerns of lower efficacy, immunogenicity, and safety. Biosimilar switching in Veterans Affairs (VA) was based on local facility policy rather than patient/provider selection and thus less prone to selection bias. The goal of this study is to evaluate the safety and effectiveness of biosimilar switching in a National U.S. Cohort of Veterans with CD and UC. Methods: We conducted a retrospective cohort study of CD and UC patients who received maintenance originator IFX from 2017-2019 in the VA. CD and UC patients were identified using a previously validated algorithm and confirmed by chart review. Patents on maintenance IFX originator were identified by dispensed medication from Corporate Data Warehouse (CDW). Patients switched to IFX biosimilar after 2017 were identified in CDW by dispensed medication and confirmed by chart review. Adverse outcomes were defined as infusion reaction, serious infection (intravenous antibiotic, delay of IFX), immunogenicity (anti-IFX antibody or IFX escalation) or disease flare (escalation of steroid, IBD related Emergency department visit, hospitalization) confirmed by chart review. Adverse event rates at 12 months for patients continued on originator IFX were compared to patients switched to IFX biosimilar using univariate and multivariate logistic regression models adjusting for patient and non-patient factors. Results: A total of 790 patients (492 CD, 298 UC) on originator IFX were identified during the study period. Of these, 380 patients were identified to have switched to IFX biosimilar and 410 patients continued on IFX originator during the study period. Overall adverse outcomes occurred in 35.6% of patients at 12 months (35.6% switch, 35.3% non-switch, p=0.87). No statistically significant difference in rates of infusion reaction, serious reaction, immunogenicity, or IBD flare were identified between switch and non-switch groups. In multivariate logistic regression including age, race, gender, concomitant medication, and VA priority status, no significant differences in adverse outcomes at 12 months were observed between switch and non-switch groups (aOR 1.09, 95% CI 0.76-1.42). Conclusion: In a real-world national U.S. cohort of patients with CD and UC, we observed IFX biosimilar switching was not associated with adverse events compared to continuation on IFX originator. While this study may be underpowered to detect such a small difference, these findings provide further reassurance that IFX biosimilar switching for CD and UC is safe and effective.